If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(r + 2) = 4(2 + -4r) Reorder the terms: 4(2 + r) = 4(2 + -4r) (2 * 4 + r * 4) = 4(2 + -4r) (8 + 4r) = 4(2 + -4r) 8 + 4r = (2 * 4 + -4r * 4) 8 + 4r = (8 + -16r) Add '-8' to each side of the equation. 8 + -8 + 4r = 8 + -8 + -16r Combine like terms: 8 + -8 = 0 0 + 4r = 8 + -8 + -16r 4r = 8 + -8 + -16r Combine like terms: 8 + -8 = 0 4r = 0 + -16r 4r = -16r Solving 4r = -16r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '16r' to each side of the equation. 4r + 16r = -16r + 16r Combine like terms: 4r + 16r = 20r 20r = -16r + 16r Combine like terms: -16r + 16r = 0 20r = 0 Divide each side by '20'. r = 0.0 Simplifying r = 0.0
| 3x=69 | | 91-3x=24x+19 | | n+14=27 | | -2x-5=9 | | n+10=18 | | 25x=10 | | 3r-5=2(4r-9) | | 12-8x=76-36x | | 5x+13=-71-7x | | 166-5x=6x+12 | | -62-2x=8-9x | | x^2+2x+11=0 | | 111-3x=33x+15 | | 7-10x=31-24x | | 6x+5=115-5x | | -162-8x=10+18 | | -4x+5y=10 | | 2(7+3r)=-r | | 4x+10=-116-10x | | -4+5y=10 | | -4(3X+5)=-116 | | 12w^2+25w+12=0 | | 5+4x=26+x | | 4x-4=13x-85 | | 3x-24x+45=0 | | 4x+39=14x-81 | | 5+2x=5x-6 | | 6x-3=14x-67 | | 6x+13=-99-10x | | -(3y+5)-(-2y-6)=-7 | | 3x+46=7x+14 | | 3x+12=60-3x |